Ecological Literacy Based on Local Wisdom of the Nias Community as a Framework for Sustainable Environmental Education - Yan Piter Basman Ziraluo; Nofamataro Zebua (Universitas Pendidikan Ganesha, 2026)
Increasing environmental degradation indicates that environmental education detached from local socio-cultural contexts remains less effective in fostering ecological awareness and behavior. This study aims to formulate a contextual framework of ecological literacy based on the local wisdom of the Nias community to support sustainable environmental education. The study employed a qualitative approach using a narrative literature review combined with content analysis. Data were obtained from the GARUDA database using the keywords “local wisdom,” “Nias,” and “kearifan lokal,” resulting in 51 articles. After applying relevance, contextual suitability, and depth criteria, 8 key articles were selected for in-depth analysis. The findings reveal that customary values, traditional ecological knowledge, and collective social practices of the Nias community play a significant role in shaping ecological awareness, environmental ethics, and community participation in conservation efforts. The study highlights that integrating local wisdom into environmental education through formal, nonformal, and community-based approaches enhances its relevance, acceptance, and sustainability. Therefore, ecological literacy grounded in the local wisdom of the Nias community offers strong potential as a conceptual framework for advancing sustainable environmental education while preserving cultural identity.